2020
DOI: 10.1177/1747021820977739
|View full text |Cite
|
Sign up to set email alerts
|

The effects of immediate versus delayed feedback on complex concept learning

Abstract: We report three experiments that examine whether immediate versus delayed feedback produce differential concept learning. Subjects were shown hypothetical experiment scenarios and were asked to determine whether each was a true experiment. Correct-answer feedback was used for all three experiments; Experiments 2 and 3 also included detailed explanations. In all three experiments, subjects who received immediate feedback were shown the correct answer after each response. In Experiments 1 and 2, subjects in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…To our knowledge, not much research has investigated the impact of trial-by-trial feedback on the accuracy of self-estimates. Single studies even suggest the opposite: Corral et al (2021) observed positive effects of global feedback at the end of a knowledge task on actual performance while not observing such effects for trial-by-trial feedback. Due to the lack of research, it is necessary to further investigate the impact of performance feedback presented with varying frequency on the accuracy of self-estimates-especially for central facets of intelligence.…”
Section: The Potential Impact Of Other Forms Of Performance Feedbackmentioning
confidence: 99%
“…To our knowledge, not much research has investigated the impact of trial-by-trial feedback on the accuracy of self-estimates. Single studies even suggest the opposite: Corral et al (2021) observed positive effects of global feedback at the end of a knowledge task on actual performance while not observing such effects for trial-by-trial feedback. Due to the lack of research, it is necessary to further investigate the impact of performance feedback presented with varying frequency on the accuracy of self-estimates-especially for central facets of intelligence.…”
Section: The Potential Impact Of Other Forms Of Performance Feedbackmentioning
confidence: 99%
“…Although the findings of the aforementioned studies support embedding Mursion™ in special education EPPs to promote the acquisition of EBPs by teacher candidates (Dawson & Lignuaris/Kraft, 2017) and novice teachers (Vince-Garland et al, 2012, 2016), the timing of feedback delivery needs further investigation. The preference for and the effectiveness of feedback delivery (i.e., immediate vs. delayed) has been a controversial topic in the field of education with some researchers supporting the use of delayed feedback (e.g., Corral, Carpenter, & Clingan-Siverly, 2021) and others proposing the delivery of immediate feedback (e.g., Fu & Li, 2020; Scheeler & Lee, 2002) to promote learning. Because the previous studies on the acquisition of EBPs during Mursion TM simulations have examined the effects of delayed feedback, it is critical that additional studies are conducted to also examine the effects of immediate feedback on the acquisition, generalization, and maintenance of EBPs by teacher candidates.…”
Section: Online Simulated Learningmentioning
confidence: 99%
“…Butler & Woodward (2018) reviewed many studies and concluded that task-level delayed feedback outperformed immediate feedback. Corral et al (2021) conducted three experiments and argued that longer intervals in delayed feedback might enhance the processing of feedback and enhance conceptual knowledge learning. Furthermore, with the development of the cognitive revolution, many laboratory studies reported that delayed feedback can be more effective in promoting long-term retention than immediate feedback (e.g.…”
Section: Introductionmentioning
confidence: 99%